Grain Yield Observations Constrain Cropland CO2 Fluxes Over Europe. Issue 12 (23rd December 2017) - Combe, M.; de Wit, A. J. W.; Vilà‐Guerau de Arellano, J.; van der Molen, M. K.; Magliulo, V.; Peters, W.
Abstract: Carbon exchange over croplands plays an important role in the European carbon cycle over daily to seasonal time scales. A better description of this exchange in terrestrial biosphere models—most of which currently treat crops as unmanaged grasslands—is needed to improve atmospheric CO2 simulations. In the framework we present here, we model gross European cropland CO2 fluxes with a crop growth model constrained by grain yield observations. Our approach follows a two‐step procedure. In the first step, we calculate day‐to‐day crop carbon fluxes and pools with the WOrld FOod STudies (WOFOST) model. A scaling factor of crop growth is optimized regionally by minimizing the final grain carbon pool difference to crop yield observations from the Statistical Office of the European Union. In a second step, we re‐run our WOFOST model for the full European 25 × 25 km gridded domain using the optimized scaling factors. We combine our optimized crop CO2 fluxes with a simple soil respiration model to obtain the net cropland CO2 exchange. We assess our model's ability to represent cropland CO2 exchange using 40 years of observations at seven European FluxNet sites and compare it with carbon fluxes produced by a typical terrestrial biosphere model. We conclude that our new model framework provides a more realistic and strongly observation‐driven estimate of carbon exchange over European croplands. Its products will be made available to the scientific community through the ICOS Carbon Portal and serve as a new cropland component in the CarbonTracker Europe inverse model. Key Points: We present a novel framework to constrain cropland CO2 exchange in Europe from crop yield observations It gives a realistic estimate of daily and seasonal cropland carbon fluxes compared to independent measurements and biosphere models Local information on sowing, irrigation, and harvesting dates could help to improve it, as well as improved modeling of soil moisture stress